The Impression of ICT in Medical Education throughout COVID-19 Pandemic: A Survey among Medical Graduates of Bangladesh (Bangladesh Journal of Medical Education, 2022)
In COVID-19 pandemic, the importance of ICT in Medical education is amplified. The purpose of the study was to assess and estimate the role and impact of ICT in relation to learning on medical education and changing behavior of the students in the period of pandemic. A questionnaire survey approach was applied amid of the Bangladeshi medical undergraduates during the period of August, 2020 to November, 2020. A Google linked structured questionnaire was used and distributed to the study population via email, messenger and WhatsApp. The questionnaire was completed by 201 medical students, with 65% were female and 35% were male students. Almost all respondents (98%) owned an android smartphone and used it to access the internet. Two-thirds (69%) of respondents have medical and health related apps in their device, with Medscape being the most widely utilized app. Respondents (49%) encountered bandwidth trouble during online class. For collaborative learning with classmates, 76% respondents favored messenger and whatsApp group. ICT knowledge should be included in the curriculum, according to 57% respondents. Over one-third participants, 37.3%, were neither satisfied nor dissatisfied. 30.8% respondents were satisfied while 19.4% were dissatisfied. The long-term benefits and problems of reforming the medical education system and utilizing ICT technologies should be considered. In this pandemic circumstance, digitalization of learning can give essential foundations for future medical education, aided by ICT tools. Our study may be used as a foundation for future research into developing digital teaching models in medical education.Bangladesh Journal of Medical Education Vol.13(1) January 2022: 58-68